Evaluating the greening agenda of festivals: The case of Sinulog - Yamagishi, Kafferine; Ocampo, Lanndon (Turyzm/Tourism, 2022)
This work advances previous work on greening festival management by using the Sinulog festiwal as a case in point, as it has conditions resonating with most festivals in the Philippines and some other emerging economies. An analysis based on strengths, weaknesses, opportunities and threats (SWOT) was constructed based on an earlier work that provided some insights on assessing the green management initiatives of the festival organization. The weaknesses in the SWOT analysis are considered inputs to a root cause analysis to identify the fundamental green management issues. The two analyses suggest that the festival organization has a limited view of the green management agenda. Four elements are found crucial for greening the Sinulog festival: crafting an environmental policy; allocating financial and human resources for implementing greening initiatives; partnership agreements with local environmental institutions; and partnership agreements with sponsors who proactively support the environmental agenda. These insights may have value for other festivals in their greening agendas.